Strength and Durability Behaviour of Nano Silica on High Performance Concrete - Jaishankar, P; T. Poovizhi, K; Saravana Raja Mohan, K (International Journal of Engineering and Technology, 2018)
Nano silica is a fine convergent material of 10-9m size.  Due to its fineness, stiffness gets increased and cracks get reduced. As nano silica is fine, the mechanical strength will be increased and the durability will also be increased. Nano silica will reduce the pores compared to nominal concrete specimens. In this to study strength and durability behaviour of M70 high performance concrete with Nano Silica as admixture partially replacing cement by 0% 5% 10% 15% 20%. The experimental investigation of sorptivity test, alkalinity measurement test, water absorption test, totally 30 cubes and 15 cylinders specimens were casting and testing for strength and durability.  Specimens namely cubes, cylinders are cured for 28 days. In standard environment, after this curing period a test to analyze the strength and durability as carried out. The strength and durability start shown in increasing trend with increase in the quantity of nano silica. XRD, XRF Techniques are used to study the micro structure of the concrete. The nano silica addition reduces the pore amount and makes the concrete denser in micro structure level, which in turn increases the strength and durability.